Pengembangan Konseling Komunitas Dengan Teknik Art Therapy Untuk Meningkatkan Kebahagiaan Lansia - Maharani, Rosalinda Putri; Azzahra, Risha Putri; Aniqotunnajma, Azmi Nabila; Julia, Celsa; M, Muslikah; Mahfud, Ashari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Elderly is a period that is definitely experienced by blessed individuals. Elderly people should live their lives with joy and peace, something like this can only be obtained when they feel healthy both physically, psychologically, and socially. Happiness is directly related to the perception and what the elderly feel about their condition. High life satisfaction in the elderly is characterized by having a positive attitude towards themselves, feeling calm, always enthusiastic in doing anything, and far from the characteristics of individuals who are depressed or depressed. In increasing the happiness of the elderly, intervention is needed by holding constructive activities that are fun and enjoyable, one of which is by doing art therapy. This study aims to determine how the development of community counseling with the application of art therapy can increase the happiness of the elderly. This study uses a conceptual method. The results show that art therapy tends to be effective in increasing the happiness of the elderly with the characteristics of not being depressed, anxious or lonely.